[Something fishy ; Clay play ; Daring DAR [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles the accusation of violation of the Anti-Pollution law by Century Tuna Corporation which dumped its waste into the Taguig River down to a fishing town in Laguna de Bay ; the story of how the Alcazaren brothers turned their talents for making clay figures into business ; and the new public trust on the Department of Agrarian Reform under Miriam Defensor Santiago after the Garchitorena land scam.
Something fishy (13 min.) -- Clay play (14 min.) -- Daring DAR (15 min.)
VHS.
Keywords: Century Canning Manufacturing Corporation; Philippines. -- Department of Agrarian Reform -- Corrupt practices; Canned foods industry -- Environmental aspects; Clay animation films -- Philippines; Pollution -- Laws and legislation -- Philippines